1992
DOI: 10.1093/nar/20.6.1393
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the rat gonadotropin releasing hormone (rGnRH) gene promoter and functional analysis in hypothalamic cells

Abstract: The gonadotropin releasing hormone (GnRH) gene encodes a protein which plays a critical role in mammalian reproductive physiology. Its expression is predominantly restricted to the hypothalamus although it has also been described in the placenta. To begin to determine the promoter elements important for tissue specific expression and to examine the mechanisms of developmental and hormonal regulation of the rat GnRH (rGnRH) gene, we cloned the rGnRH gene from a rat liver genomic DNA library. The nucleotide sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 56 publications
2
54
0
Order By: Relevance
“…Cells were also transfected with 0.1 g of RSV␤gal to control for transfection efficiency. Cells were harvested 16 -18 h post-transfection and assayed for luciferase and ␤-galactosidase activities as described previously (37). Statistical Analysis-Comparisons between ethanol control, and 5␣-DHT-treated samples were analyzed using unpaired t test using GraphPad InStat version 3.02 for Windows, GraphPad Software, San Diego, CA.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were also transfected with 0.1 g of RSV␤gal to control for transfection efficiency. Cells were harvested 16 -18 h post-transfection and assayed for luciferase and ␤-galactosidase activities as described previously (37). Statistical Analysis-Comparisons between ethanol control, and 5␣-DHT-treated samples were analyzed using unpaired t test using GraphPad InStat version 3.02 for Windows, GraphPad Software, San Diego, CA.…”
Section: Methodsmentioning
confidence: 99%
“…A HindIII fragment containing nucleotides Ϫ3026 to ϩ116 of the rat GnRH promoter was ligated into the HindIII site of pA 3 LUC (rGnRH-LUC), placing the GnRH promoter upstream from the LUC coding region (10). PRK5-Ark contains the mouse Ark cDNA and was provided by Paola Bellosta (New York University) (17).…”
Section: Methodsmentioning
confidence: 99%
“…The total amount of plasmid was maintained constant at 20 -25 g with the inclusion of the appropriate empty vector. Cells were harvested 16 -18 h posttransfection, and the lysate was assayed for LUCand ␤-gal activities as described previously (10). For the MEK1-R4F, MEK1-8E, MEK5(D), and MEK5(A) transfections, 3-10 g of plasmid was added to the assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using immortalized GnRH1 releasing cell lines (GT1-7) (Liposits et al, 1991;Mellon et al, 1990;Weiner et al, 1992;Wetsel, 1995), a proximal promoter Kepa et al, 1992) and distal enhancer regions (Kepa et al, 1996;Lawson et al, 1996;Whyte et al, 1995) critical for mammalian GnRH1 gene regulation have been identified. The proximal promoter is important for basal GnRH1 gene expression and the distal promoter for GnRH1 neuron-specific expression because of an enhancer region.…”
Section: Introductionmentioning
confidence: 99%